지형학적 특성을 고려한 레이더 강수량 편의보정 매개변수의 변동성 및 불확실성 분석 - 김태정; 반우식; 권현한; Kim, Tae-Jeong; Ban, Woo-Sik; Kwon, Hyun-Han (Journal of Korea Water Resources Association, 2019)
Various applications of radar rainfall data have been actively employed in the field of hydro-meteorology. Since radar rainfall is estimated by using predefined reflectivity-rainfall intensity relationships, they may not have sufficient reproducibility of observations. In this study, a generalized linear model is introduced to better capture the Z-R relationship in the context of bias correction within a Bayesian regression framework. The bias-corrected radar rainfall with the generalized linear model is more accurate than the widely used mean field bias correction method. In addition, we analyzed variability of the bias correction parameters under various geomorphological conditions such as the height of the weather station and the separation distance from the radar. The identified relationship is finally used to derive a regionalized formula which can provide bias correction factors over the entire watershed. It can be concluded that the bias correction parameters and regionalized method obtained from this study could be useful in the field of radar hydrology. 최근 수문기상학 분야에서 레이더 강수량을 활용한 응용연구가 활발하게 진행되고 있다. 하지만 레이더 강수량은 경험적인 레이더 반사도-강수강도 관계식을 활용하여 레이더 강수량을 추정하기 때문에 실제 지상에 도달하는 강수량과 정량적인 오차가 필연적으로 발생한다. 따라서 본 연구에서는 레이더 강수량 편의보정을 위하여 Bayesian 추론기법과 일반화 선형모형을 연계하여 불확실성을 고려한 편의보정 매개변수를 산정하였다. 일반화 선형모형을 적용한 레이더 강수량 편의보정 결과는 현재 널리 사용되고 있는 평균보정 기법보다 우수한 통계적 효율기준을 제시하였다. 추가로 지형학적 특성에 따른 편의보정 매개변수의 변동성을 분석하여 고도 및 이격거리에 따른 편의보정 매개변수의 지역화 공식을 제시하였다. 본 연구를 통하여 개발된 레이더 강수량 편의보정 매개변수 산정 및 지역화 결과는 레이더와 관련된 다양한 연구에 활용성이 클 것으로 판단된다.